Suchozemští plži přírodní rezervace Plané loučky a přírodních památek Častava, Hvězda a Kurfürstovo rameno v CHKO Litovelské Pomoraví - Radovan Coufal (Malacologica Bohemoslovaca, 2022)
In 2022, four small-scale protected areas (SPA) within Litovelské Pomoraví Protected Landscape Area were surveyed for terrestrial molluscs. All localities are floodplain forest fragments with oxbow lakes, pools and marshes in the Morava river catchment. The most species-rich SPA was Hvězda Natural Monument (NM), with 38 species recorded. The threatened species Cochlicopa nitens (Endangered), known from this area from previous surveys, was not recorded despite high sampling effort. This sensitive hygrophilous species disappeared probably due to droughts occurring in earlier years. However, other sensitive hygrophilous species such as Euconulus alderi (Nearly Threatened) and Vertigo antivertigo were recorded. The latter was also found in Plané loučky Nature Reserve (NR; 27 spp. in total) and Častava NM (19 spp. in total). Relatively common floodplain forest species Perforatella bidentata was recorded in Plané loučky NR and Hvězda NM; however, it was absent in Častava NM and Kurfürstovo rameno NM (20 spp. in total). The partial absence of this species and the complete absence of substantially declining floodplain species Pseudotrichia rubiginosa (Nearly Threatened) and other sensitive taxa indicate habitat degradation caused mainly by stream regulations and water level decrease and manipulation. The presence of invasive plant species known to decrease terrestrial mollusc species diversity and abundance are of the essence as well. Highly invasive species Arion vulgaris was the most abundant species in all of the surveyed SPAs, except for Hvězda NM, where it was present in lower numbers. Over some twenty years, this species spread from anthropogenic areas to natural habitats to become one of the most prominent features of floodplain biocoenoses in Litovelské Pomoraví and elsewhere. To improve the habitat conservation status, it is important to maintain favourable water level in streams and water bodies adjacent to SPAs, especially during the critical periods of summer droughts. Furthermore, it is advised to focus the management on neophyte extirpation.